Lateral turbulent mixing forces in the long shore current calculation by Longuet-Higgins method and their influence on long shore sediment transport - Hung, Nguyen Manh (Vietnam Journal of Mechanics, 2003)
Longuet - Higgins method for long shore current and Bijker method for sediment transport calculations are worldwide used mathematical model in the coastal engineering. When using them, we should image how work the methods and what is sensitivity and influence of each parameters on final results as sediment transport. In this paper, the influences of parameters N, P of lateral turbulent mixing forces on the long shore current and then on the sediment transport are estimated. The Bijker example is used and the computation results are compared with Bijker results for neglecting the lateral turbulent mixing. A field application with appropriate parameters N and P for Le Thuy beach is obtained for verification of long shore current and sediment transport.